Landasan Filosofis dan Teoristik Teknologi Pembelajaran di MA Muhammadiyah - Muhammad Rais Shidiq; Afiful Ikhwan (Jurnal Pendidikan Nusantara, 2023)
This article examines the philosophical and theoretical foundations that underpin economic growth and the development of educational technology. The main aim of this research is to explain the relevance of educational philosophy and theory in the context of using technology to improve student achievement. Constructivism, behaviorism, and humanism are some of the main philosophical strands, while constructivism, cognitivism, and social learning theories are the main educational theories studied. The current methodology for conducting research combines literary criticism and critical analysis of the theory and practical applications used in educational technology. The results of this study indicate that a strong educational philosophical understanding is an important element in the development of effective teaching technology. In addition, the proper integration of learning theory into the design and application of teaching technology can improve student interaction, participation, and use of materials. The research findings have important implications for educational practice and advances in teaching technology. They hope to incorporate philosophical and theoretical foundations into the development and application of educational technology to create responsive, inclusive and effective learning environments. It is important to carry out longer studies and undertake exploratory research to fully understand the implications of this concept and evaluate its impact on rigorous and high-quality undergraduate education